2004
DOI: 10.1167/iovs.03-1046
|View full text |Cite
|
Sign up to set email alerts
|

Image Defocus Modulates Activity of Bipolar and Amacrine Cells in Macaque Retina

Abstract: This was the first evidence of focus-dependent activation of bipolar as well as amacrine cells in a primate retina. Focus-sensitive neurons are candidates for roles in vision-dependent regulation of eye growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 73 publications
2
55
0
1
Order By: Relevance
“…Such animal models are not comparable to normal humans with simple myopia. Studies in traditional defocused animal models suggested that a +3.00 D hypermetropic defocus in one eye could induce elongation of the vitreous chamber in the defocused eye when the function of both eyes was balanced [23,24,26,36,37]. The main rationale was that, during binocular imaging, the defocused eye was passively remolded to achieve the same clear image as that by the control eye, which resulted in passive elongation of the vitreous chamber and the ocular axis [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such animal models are not comparable to normal humans with simple myopia. Studies in traditional defocused animal models suggested that a +3.00 D hypermetropic defocus in one eye could induce elongation of the vitreous chamber in the defocused eye when the function of both eyes was balanced [23,24,26,36,37]. The main rationale was that, during binocular imaging, the defocused eye was passively remolded to achieve the same clear image as that by the control eye, which resulted in passive elongation of the vitreous chamber and the ocular axis [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that we may be able to prevent the occurrence and development of myopia by blocking such aforementioned factors. Animal models of myopia have been made using form-deprived and hypermetropic defocusing stimuli [21][22][23][24][25][26][27][28][29][30]. Francis used a method of restricted visual space to induce myopia in young rhesus monkeys, but this technique did not eliminate the potential interference of form deprivation factors, and thus could not accurately simulate the development of myopia in adolescence [31].…”
mentioning
confidence: 99%
“…14 A link between Egr-1 (called ZENK in chicks) expression levels and retinal image quality has also been described in mice 15 and macaques. 16 Moreover, glucagon mRNA and peptide levels in the retina are altered by treatment with spectacle lenses in a sign-of-defocus-dependent manner. Glucagon, as well as glucagon agonists, inhibited lens-induced myopia development.…”
mentioning
confidence: 99%
“…Here, it is localized to glutamic acid decarboxylase-65 immunoreactive amacrine cells (GAD65) rather than to glucagon [42]. Recently, receptors of GLP-2 were localized by immunohistochemical staining in lens and cornea of the mouse [17], and Feldkaemper et al [10] found the mRNA of both the glucagon receptor and of preproglucagon in retina.…”
Section: Introductionmentioning
confidence: 99%